Gap analysis tools - viewer software architecture document - Nasayo, Carlos; Mendez, Andres; Diaz, Maria Victoria; Hernandez, Victor; Lopez, Sebastian; Ramirez Villegas, Julian; Sotelo, Steven (2024)
This document provides the results of the requirements analysis for a Gap Analysis results visualization system. The system is intended to serve as a tool to plan the collection of genetic material in areas where it has not been collected yet, by generating routes that will pass through different locations entered by the user. This document follows some of the guidelines of the C4 model to define the architecture of the systems at different levels.